Synthesis, Characterization and Biological Activities of New Azo Dyes -Azomethine Compound and Their Metal Complexes - Rehab Al-Hassani (Journal of Global Pharma Technology, 2018)
The new ligand (2-thioxo-5-((4-(1-(p-tolylimino) ethyl) phenyl) diazenyl) dihydropyrimidine-4, 6(1H, 5H)-Dione (R1) have been synthesized and characterized by micro elemental analysis, Mass, (1H-13C) NMR, FT-IR, and UV-Vis spectroscopic techniques. (R1) acts as a ligand coordinating with some metal ions Co(II), Ni(II), Cu(II), Au(III) and Pt(IV) generated fife mononuclear metal complexes, represented as [CoR1Cl2(H2O)2] (a) , [NiR1Cl2] (b) , [CuR1Cl2] (c), [Pt(R1)2Cl2]Cl2(d) , [Au(R1)2]Cl3(e) .The Structures of the new compounds were characterized by elemental , FT-IR and UV-Vis Spectra. The magnetic properties and electrical conductivities of metal complexes were also determined. The antibacterial activity for the (R1) and its metal complexes were studied against two types of pathogenic bacteria (Escherichia coli, and Staphylococcus aureus) Furthermore, the antifungal activity against two fungi) Candida albicans, and Aspergillusflavus (was studied for (R1) and its metal complexes. The anticancer activities of the ligand and their metal complexes have been extensively studied on The La cancer cell line.